Hubungan Antara Pengetahuan Tentang Kesehatan Reproduksi Dengan Pernikahan Dini Di Kecamatan Selajambe Kabupaten Kuningan Periode 2018-2019 - Dwi Rusmilia, Dea Setia (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Background : Early marriage according to Law number 16 of 2019 paragraph 7 mentioned marriage is allowed if men and women reach the age of 19 years. In Kuningan Regency, there is an increase in the early marriage incidence in 2016 to 2019. Cases of early marriage based on data in Religious Affair Office of Selajambe subdistrict as much as 18% including the high category of all marriages that occurred entered into early marriage in 2019. There is a match between the data obtained from Selajambe Primary Health Facility and Religious Affair Office of Selajambe subdistrict, i.e. the level of young marriage with the number of pregnancies in women aged ? 20 years. This study aims to find out the relationship between reproductive health knowledge and the rate of early marriage in Selajambe Subdistrict Kuningan Year 2020. Method : This research used quantitative analytical research with correlation research design, and cross sectional approach method. Research population is newly married women in 2018 to 2019 period, using purposive sampling techniques. Research sample of 30 respondents. Instruments used are questionnaires. Analysis of data used univariate and bivariate with Chi-Square test (X2) with (?) 0.05 degree of meaning. Research results : Most respondents aged > 20 years as many as 12 people (40%), and educated elementary / junior high school as many as 23 people (76.7%). Most married respondents have sufficient knowledge of reproductive health. The result of statistical analysis of Chi square obtained a value of p value 0.042 smaller than (?) 0.05. Conclusion : There is a relationship between knowledge about reproductive health and the level of early marriage in Selajambe Subdistrict, Kuningan District in 2020.